(untitled) (ZOO-Journal, 2019)
Present study deals with fish diversity along with management aspects of lakes in Pokhara Valley. It was conducted during September 2009 to February 2010. Monthly fish sampling was done using gill net with the help of experienced fishermen. Altogether 34 species of fishes were recorded in the present study. The population status of important fish species viz., Tor Tor (Hamilton- Buchanan) was found to be endangered, that of Tor putitora (Hamilton-Buchanan), Neolissocheilus hexagonolepis (Mc Clelland), Chagunius chagunio (Hamilton-Buchanan), and Brachydanio rerio (Hamilton-Buchanan) were found to be vulnerable (VU); five species were uncommon (UN) and 24 species were common (C) including common exotic(C*). The lakes were found to be influenced by human activities such as direct disposal of domestic sewage, unscientific agricultural practices, construction of dams without fish ladder or passes, deforestation causing soil erosion etc., which were creating threat to the lentic ecosystem.